2020
DOI: 10.19053/22160159.v11.n27.2020.10613
|View full text |Cite
|
Sign up to set email alerts
|

Conocimiento didáctico del contenido y enseñanza de la filosofía

Abstract: Se presentan los resultados del proyecto de investigación Balance de la enseñanza de la filosofía en Colombia entre práctica y experiencia, a partir de problematizaciones epistemológicas que delimitan el objeto de la didáctica general y del encuentro con el emergente conocimiento didáctico del contenido [CDC], que plantea la necesidad de configurar una didáctica de la filosofía y sus conceptualizaciones. Se utiliza el modelo de Park y Oliver para analizar el CDC en clases de filosofía. La intención es valorar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…La enseñanza de la filosofía desde la perspectiva francesa, inicialmente, consistía en la lectura, comentario de textos filosóficos, y disertación, que permitía a los estudiantes realizar una exposición argumentativa sobre un tema o cuestión problemática, y comparar la postura de distintos filósofos (Gómez, 2008;Mariño et al, 2016;Cruz et al, 2020a). En este sentido, el objetivo de la enseñanza de la filosofía en el nuevo mundo fue formar sujetos con pensamiento crítico, capaces de intervenir la realidad.…”
Section: La Disertación Filosóficaunclassified
“…La enseñanza de la filosofía desde la perspectiva francesa, inicialmente, consistía en la lectura, comentario de textos filosóficos, y disertación, que permitía a los estudiantes realizar una exposición argumentativa sobre un tema o cuestión problemática, y comparar la postura de distintos filósofos (Gómez, 2008;Mariño et al, 2016;Cruz et al, 2020a). En este sentido, el objetivo de la enseñanza de la filosofía en el nuevo mundo fue formar sujetos con pensamiento crítico, capaces de intervenir la realidad.…”
Section: La Disertación Filosóficaunclassified
“…The development of teaching expertise is a central topic of current discussion in nursing education. It has been shown that, for nursing teaching practice, clinical experience 1 or postgraduate training in education (masters or doctoral degrees) are not enough by themselves, 1 , 2 since general didactics does not cover the specificities necessary to teach the concepts inherent to each discipline. 2 The role of the nursing professor implies not only having professional practice competence, which is what provides knowledge on the subject, but also developing knowledge and skills regarding the specific ways nursing is taught, learned, and evaluated; 1 since, as any other discipline, it requires specific knowledge that responds to its own pedagogical needs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, for nursing teaching practice, clinical experience 1 or postgraduate training in education (masters or doctoral degrees) are not enough by themselves, 1 , 2 since general didactics does not cover the specificities necessary to teach the concepts inherent to each discipline. 2 The role of the nursing professor implies not only having professional practice competence, which is what provides knowledge on the subject, but also developing knowledge and skills regarding the specific ways nursing is taught, learned, and evaluated; 1 since, as any other discipline, it requires specific knowledge that responds to its own pedagogical needs. This is the Pedagogical Content Knowledge (PCK), which, according to Shulman 3 represents “the blending of content and pedagogy into an understanding of how particular topics, problems, or issues are organized, represented, and adapted to the diverse interests and abilities of learners.” PCK analysis allows establishing the relationship that exists between scientific, pedagogical and didactic knowledge in the teaching of any discipline, 4 and it is easily identifiable in an expert professor, 3 who stands out for having extensive knowledge about the topics, about the strategies for teaching them, and about the students and their prior knowledge 4 , to transform them into pedagogical representations and actions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations